Pengaruh Jenis Aerator Dan Media Filter Dalam Menurunkan Kadar Besi (Fe) Air Sumur - Megananda, Reza; Badriani, Ririn Endah; Dhokhikah, Yeny (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2023)
The conversion of agricultural land into residential areas will have an impact on the need for clean water which contains various metal contaminants such as iron. One of them is the Randu Housing, Sumberejo Village, Sukodono District, Lumajang Regency, which is one of the many housing estates built from former rice fields. This study aims to analyze the effect of using types of aerators, namely cascade aerators and bubble aerators with a variety of filter media using dune sand and river sand with a discharge of 1 liter/minute. This type of research uses an experimental method which is carried out on a laboratory scale. The results showed the percentage reduction in Fe content in aeration treatment using cascade aerator and bubble aerator was 14,55% and 2,16%, sedimentation treatment was 3.34%, and filtration treatment using dune sand and river sand filter media was 81,85% and 89.13%. The results of the analysis showed that the variables of the cascade aerator, dune sand filter and river sand filter had a significant relationship with the decrease in iron content. While the relationship that does not have a significant effect is the bubble aerator and sedimentation variables. Keywords: Aeration, Sedimentation, Filtration and Iron (Fe)